Analysis Of Models In Development In Information Systems - Aswati, Safrian; Mulyani, Neni; Amin, Muhammad; Firmansyah, Ada Udi; *, Suhendra (IJRDO -Journal of Computer Science Engineering, 2017)
Development of information technology nowrequires organizations, companies or otherinstitutions to follow these developments. Onemanifestation of the development of informationtechnology is with the existing software that cansimplify the data processing jobs. The software isin the form of information systems. Informationsystems can replace existing systems in theorganization in terms of data processing. Whenthe system will be developed into an informationsystem required models in its development. Thesesystem development models provide detailedsteps to produce a quality information system.There are many models used in systemdevelopment such as Waterfall, Spiral, RapidApplication Development (RAD), The OpenGroup Architecture Framework (TOGAF),Zachman and COBIT. Each of these modelsprovides different stages in system development.The main pillar of this model is the SystemDevelopment Life Cycle (SDLC) which can beassumed as a classical methodology in systemdevelopment. In this study the authors analyzesome of the models used in system developmentLater this model can be used as a reference of asystem analyst when will develop the system.